Leasing Company Responsibility for Embezzlement of Payments by Employees - Adi Wiranata, Rio; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze: 1). The form of legal responsibility of leasing companies for the act of embezzlement of credit payments committed by certain employees in employment relationships. 2) Legal protection for leasing consumers who are harmed due to payments that are not administratively recognized by the company, as occurred in the case of PT Mega Centra Finance in Pekalongan City. This type of research is included in the scope of normative legal research. The approach method in this study is Legislation and conceptual The type of data in this study is secondary. Secondary data sources consist of primary, secondary and tertiary legal materials. The method of data collection in this study is by using library techniques (document study). The analysis in this study is qualitative-normative. The results of the study concluded: 1). The form of legal responsibility of leasing companies for the act of embezzlement of credit payments by employees reflects the application of the principle of corporate liability which includes civil, criminal, and administrative aspects. In civil law, responsibility is based on Article 1367 of the Civil Code concerning the responsibility of employers for the actions of their subordinates. In criminal law, Articles 45 and 46 of Law No. Law No. 1 of 2023 (the new Criminal Code) allows corporations to be held accountable if negligence in the supervisory system triggers a criminal act. Meanwhile, administratively, POJK No. 35/POJK.05/2018 emphasizes the obligation of financing companies to implement the principle of prudence and consumer data protection. Thus, companies remain responsible for consumer losses as long as the employee's actions are carried out within the employment relationship. 2.) Legal protection for leasing consumers who suffer losses due to administrative non-recognition of payments includes two forms: preventive and repressive. Preventive protection is carried out through the application of prudential principles and internal supervision as stipulated in the UUPK and POJK, while repressive protection aims to restore consumer rights through complaint mechanisms, mediation, civil lawsuits, and criminal sanctions for perpetrators. The principle of vicarious liability ensures the company's legal responsibility for the actions of employees who are still within the scope of employment. The effectiveness of this legal protection depends on the implementation of good corporate governance and consistent law enforcement to ensure legal certainty for consumers.